Tipología familiar y su influencia en el consumo de alcohol en estudiantes de bachillerato. Salcedo, 2022. - Jenny Roció Tenezaca Sánchez (2022)
ABSTRACT: The objective of this research was to analyze the family typology and its influence on alcohol consumption in high school students of the ‘’19 de Septiembre’’ Educational Unit in the city of Salcedo. A descriptive, correlational, bibliographic, bibliographic, no experimental, cross sectional study was carried out. We worked with a population of 440 records of high school adolescents and a non-probabilistic sample of 215 records. In order to investigate the study variables, documentary analysis was used as a technique and as an instrument, the data recording form was used to collect important data on the family typology of the adolescents and the results of the AUDIT test, in order to identify the types of family and their influence on alcohol consumption. Among the main results regarding family typology, it was found that adolescents live in a nuclear family (56.3%), three generations (16.3%) and a single-parent family (14%); in the AUDIT test, no gender differentiation was found, 19.1% of the population is a risk drinker, and 14% have physical-psychic problems with drinking and probable alcohol dependence. In the correlation a critical value of Rho was obtained is 0.20 with a significance p < 0.05 that is, there is a positive association between the two study variables. Therefore, it can be concluded that the types of family in which the adolescents live are nuclear, threegeneration and single-parent families. Alcohol-related problems are observed in 33.1% of the young people and the family typology is related to alcohol consumption. Key words: family, family typology, alcohol consumption, adolescents